Feasiblestudy of modifier induction motor for low speed renewable energy generator - Poungching-nyam, Arnon (RMUTSB ACADEMIC JOURNAL, 2016)
This research presents a study on value added of used induction motors. The induction motor utilization and the efficiency of motor are typically decreased according to operating time. The efficiency reduction affects to the higher energy consumption to maintain the normal operating conditions. The structure of the used induction motor cannot apply due to deterioration or low efficiency used to modifier for low speed renewable energy generator; however it has a potential for renewable resource generator that mostly requires low prime mover speed. In remote rural area, the electricity from grid is not sufficient to the economic reason. This research proposes the structural change to the used induction motor to rebuild the low speed renewable resource generator by rewiring the new coil in the motor stator and adding permanent magnets embedded in the rotor of the induction motor. In addition, the preliminary test of the induced electric production and efficiency in turns coils between single phase and three phases show the proposed generator that can produce expected voltage at low speed with acceptable designed power. Moreover, the efficiency of three phase generator is higher than the single phase generator with the same rating. Finally, the parameter of propose generator will be discussed to enhance the performance of the low speed renewable resource generator.